2019
DOI: 10.1002/adsc.201900370
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Dehydrogenative C−O Coupling of Oximes with Acetonitrile, Ketones and Esters

Abstract: A transition metal‐free approach for the generation of radical intermediates via EDA complexes had been developed. This approach enables a cross‐dehydrogenative C−O coupling of oximes with acetonitrile, ketones and esters with high yields and regioselectivities. Perfluorobutyl iodide was used as the unique electron acceptor to trigger a new radical formation. The radical pathway was confirmed by UV‐Vis spectroscopy, radical inhibiting, trapping and kinetics experiments.magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 59 publications
0
25
0
Order By: Relevance
“…These above methods necessitate expensive Ir/Ru organometallic complexes and transition‐metal catalyst, which bring about some limitations, such as toxicity and metal contamination. Very recently, ultraviolet (UV) light‐induced‐coupling of sulfinates and arylhalides was reported . The high‐energy UV light is incompatible with some functional groups and leads to side reactions.…”
Section: Methodsmentioning
confidence: 99%
“…These above methods necessitate expensive Ir/Ru organometallic complexes and transition‐metal catalyst, which bring about some limitations, such as toxicity and metal contamination. Very recently, ultraviolet (UV) light‐induced‐coupling of sulfinates and arylhalides was reported . The high‐energy UV light is incompatible with some functional groups and leads to side reactions.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the oxidative C-O coupling of oximes with acetonitrile, esters 52, and ketones 53 was realized [95] (Scheme 21). The authors suggested a radical mechanism in which the iminoxyl radical is generated from the oxime anion under the action of perfluorobutyl iodide through the formation of an EDA complex (electron donor-acceptor complex, which is also called charge-transfer complex).…”
Section: Scheme 18mentioning
confidence: 99%
“…The choice of the base was crucial and the best results were obtained with Cs 2 CO 3 and K 2 CO 3 , whereas Na 2 CO 3 gave only low yields under otherwise identical conditions. The same catalytic system also works for the C–S coupling of aryl halides and sulfinate salts …”
Section: Photocatalyst‐free Carbon–heteroatom Coupling Reactionsmentioning
confidence: 99%